PENGARUH MEDIA SOSIAL TERHADAP PERILAKU AKHLAK SISWA SEKOLAH MENENGAH - Hasballah; Ainal Mardhiah; Masbur; Mashuri (Institut Ummul Quro Al-Islami Bogor, 2025)
This study aims to analyze the effect of social media use on the moral behavior of high school students in Banda Aceh. Social media has become an integral part of teenagers' lives and has a significant influence on their mindset, attitudes, and social interactions. Although it can be a means of learning and self-expression, excessive use of social media without supervision can have a negative impact on students' moral and spiritual development. This study uses a quantitative approach with a survey method by distributing questionnaires to a number of high school students in the Banda Aceh area. The data obtained were analyzed using a simple linear regression test to determine the relationship between the intensity of social media use and students' moral behavior. The results of the study show a significant relationship between the two variables, where the higher the intensity of social media use, the lower the level of politeness, responsibility, and empathy among students. However, this study also found that social media can have a positive impact if used in an educational and creative manner. Therefore, effective supervision and guidance from parents are needed, as well as the role of schools in instilling digital literacy and character education so that social media becomes a means of positive moral formation.